Enhancing Early Reading Skills Through Picture-Based Contextual Learning for At-Risk First-Grade Students - Silvia, Silvia; Ishartiwi , Ishartiwi (Papanda Publisher, 2025)
Early reading skills represent fundamental competencies essential for elementary students' academic success, yet substantial gaps persist in effective interventions for at-risk learners. This study investigated how picture-based contextual learning media enhances early reading skills among first-grade students with learning difficulties. This classroom action research employed Kemmis and McTaggart's spiral model, conducted at SDN 006 Telen with 15 first-grade students (9 female, 6 male), including two students with learning difficulties. The intervention utilized picture-based contextual learning media across two complete cycles, each comprising three meetings with systematic planning, implementation, observation, and reflection phases. Data collection employed reading competency tests and structured observation sheets, analyzed using quantitative descriptive techniques including N-Gain calculations and qualitative analysis of behavioral observations. The intervention demonstrated remarkable effectiveness, progressing from baseline conditions where only 30% of students recognized vowels to achieving 93.33% competency by Cycle 2. Pre-test scores averaged 40, improving to post-test scores of 87, representing 117.5% improvement. The N-Gain score of 0.78 indicated high intervention effectiveness. Beyond cognitive improvements, students demonstrated enhanced motivation, self-confidence, and psychomotor skills development. The findings validate theoretical frameworks including Paivio's dual coding theory and constructivist learning principles while providing empirical evidence for integrating visual media with contextual learning approaches. The research contributes practical, accessible interventions that regular classroom teachers can implement for at-risk populations, supporting inclusive education initiatives and early literacy intervention programs across diverse educational contexts.